2015
DOI: 10.1016/j.saa.2015.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X-ray crystal structure, thermal behavior and spectroscopic analysis of 1-(1-naphthoyl)-3-(halo-phenyl)-thioureas complemented with quantum chemical calculations

Abstract: Two novel 1-(1-naphthoyl)-3-(halo-phenyl) substituted thioureas, namely 1-(1-naphthoyl)-3-(2,4-di-fluoro-phenyl)-thiourea (1) and 1-(1-naphthoyl)-3-(3-chloro-4-fluoro-phenyl)-thiourea (2), were synthesized and fully characterized. The X-ray crystal and molecular structures have been determined resulting in a planar acylthiourea group, with the C=O and C=S adopting a pseudo-antiperiplanar conformation. An intramolecular N-H⋯O=C hydrogen bond occurs between the thioamide and carbonyl groups. The crystal packing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 59 publications
6
17
0
2
Order By: Relevance
“…This assignment is in agreement with those previously reported for related substituted thioureas [39,63]. This assignment is in agreement with those previously reported for related substituted thioureas [39,63].…”
Section: Vibrational Analysissupporting
confidence: 94%
“…This assignment is in agreement with those previously reported for related substituted thioureas [39,63]. This assignment is in agreement with those previously reported for related substituted thioureas [39,63].…”
Section: Vibrational Analysissupporting
confidence: 94%
“…Both the co-crystal and the previously reported N -carbamothioylacetamide have the same space group of P -1 [ 30 ]. However, further literature search revealed that the crystal structure of the ring-substituted thiourea compounds are available [ 31 , 32 ]. The structure reported in this reference (CDS refcode KECHIJ01 and deposition number 1009665) [ 30 ], was the only structure which shared very close identities with the titled co-crystal, asides from the others with ring structures and thiourea moieties, whose properties have been well documented [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure depicts the experimental UV‐Vis spectra of both compounds in Dimethyl sulfoxide (DMSO) in the 230–800 nm range. The spectra are also evaluated from the calculated vertical electronic transitions energies and oscillator strengths between the initial and final states . The assigned transitions with major contributions for I and II are shown in Table and the character of the orbitals involved in the main electronic transitions for compounds I and II are shown in Figure for a better description of the electronic properties.…”
Section: Resultsmentioning
confidence: 99%